Constructing the Green Campus within the Internet of Things Architecture - Hsing-I Wang (International Journal of Distributed Sensor Networks)
The “Internet of Things” radically changes the view of the “Internet” by embracing every physical object into network. The vision of “IoT” promises to enhance the capabilities of objects and forms a smart environment so that people will benefit from the IoT revolution. As the global population grows, the resources on earth are depleted quickly. In order to have a sustainable earth, governments around the world put a lot of efforts to advocate the reduction of carbon production as well as to emphasize the benefits of reducing the consumption of energy. The proposition has been promoted on campus of educational institutions as well. Smart campus is a trendy application in the paradigm of the IoT. This research adopts the concept of the “Internet of Things” to construct a green campus environment which will realize the idea of energy saving. The architecture of the construction of green campus is established and three application systems have been developed as well. The efforts of this work allow the campus to manage the computer labs and the air conditioners more efficiently. The sensor network will save more energy since data are reported periodically and the analysis will be carried out in time to locate the problems.